Sunflower effect: enhancement of laser-pulse-induced impulse in the beam incident direction due to surface undulation. (24th May 2019) - Katagiri, Yusuke; Sasoh, Akihiro
Abstract: An impulse generated by laser ablation bas been implicitly assumed to be directed in the normal direction to the irradiation surface. In this study, however, the impulse induced by an Nd:YAG laser pulse with a wavelength of 1.064 μ m irradiated on to a macroscopically flat aluminium plate ablator was enhanced in the direction of the laser beam incidence due to microscopic surface undulation, the characteristic height and pitch of which are tens of the beam wavelengths. The inner product of the incident laser beam vector and the normal vector to the surface is locally enhanced on the 'sunny' side. In the vapor regime in which the impulse is an increasing function of the fluence, the effective fluence and the impulse component in the incident direction are enhanced. With repetitively irradiating laser pulses on to the same spot with a fluence of 4.5 J cm −2 nominal to a macroscopically flat surface, the impulse gradually increased due to this 'sunflower' effect, then became saturated. The momentum coupling coefficient in the saturation stage became an increasing function of the angle of incidence. This impulse performance will become considerably important in the application of laser ablation to the remote motion control or even deorbiting of space debris.